2014
DOI: 10.21082/ijas.v15n2.2014.55-64
|View full text |Cite
|
Sign up to set email alerts
|

IMPROVEMENT OF EARLY MATURITY IN RICE VARIETY BY MARKER ASSISTED BACKCROSS BREEDING OF Hd2 GENE

Abstract: Early-maturing and high-yielding rice variety is very useful for increasing rice production in Indonesia. The aim of this research was to develop new lines of Indonesian rice containing Hd2 gene using Code variety as a recipient parent and Nipponbare variety as a donor parent through targetted MAB approach using RM1362 and RM7601 in chromosom 7 for foreground selection. After two generations of backcrossing, the positive alleles of Hd2 gene from Nipponbare had successfully trans-ferred into Code. The plant num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Six lines flowered earlier 5 days than Conde in Sukamandi and three lines flowered earlier 3 days in Maros. In line with Prasetiyono et al (2014) reported that the earliest flowering line in the improved Ciherang was 4 days earlier than Ciherang. Yamamoto et al (1998) reported that large variation in days to heading of Hd2 was observed in the population of crossing between Nipponbare and Kasalath.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Six lines flowered earlier 5 days than Conde in Sukamandi and three lines flowered earlier 3 days in Maros. In line with Prasetiyono et al (2014) reported that the earliest flowering line in the improved Ciherang was 4 days earlier than Ciherang. Yamamoto et al (1998) reported that large variation in days to heading of Hd2 was observed in the population of crossing between Nipponbare and Kasalath.…”
Section: Discussionmentioning
confidence: 62%
“…SSR Primer RM20582 (F: AGAGCGTCGTCCTTCACCATCC and R: GGCCAATACGACGATACATTACACG) linked to Xa7 locus located on chromosome 6 at the genetic distance of 118,5 cM (Chen et al, 2008). For the background selection: two hundred and fourty three polymorphic SSR primers distributed on 12 chromosomes (Fatimah et al, 2014) were used for background selection. Amplified products was separated by electrophoresis in 8% polyacrylamide gel (Dual Triple-Wide Mini-Vertical System, C.B.S.…”
Section: Molecular Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Local black rice cultivars often have low yield potential (3-4 Mg per ha) (Fatimah et al, 2014;Wiranti et al, 2015), higher plant habit, and long harvesting date (≥ 150 days) (BB Padi, 2009). Improving black rice cultivar can be done by crossing it with superior cultivars with better agronomic characteristics.…”
Section: Introductionmentioning
confidence: 99%